Introduction - A moment to mark: the Brazilian Constitution turns 30 - Albert, Richard; Ranchordás, Sofia; Velasco Rivera, Mariana (Revista de Investigações Constitucionais, 2018)
An introduction from the Guest Editors to the Thematic Dossier "The 30th Anniversary of the 1988 Brazilian Constitution" of the Journal of Constitutional Research (Revista de Investigações Constitucionais), vol. 5, n. 3, 2018.